Thrust geometries and evolution of the eastern North Potwar Deformed Zone, Pakistan - Jadoon, Ishtiaq A.K.; Khawaja, Azam A.; Jamshed, Syed Q. (Journal of Himalayan Earth Sciences, 1995)
The North Potwar Deformed Zone is part of the active Himalayan foreland fold and-thrust belt in northern Pakistan. Field work have been carried out mostly along a profile in the eastern North Potwar Deformed Zone, to gain an insight into this complexly deformed area of hydrocarbons interest. The results show a triangle zone geometry and a set of imbricates between the Soan Syncline and the Main Boundary Thrust. The preserved triangle zone below the Soan Syncline is characterized by a floor thrust located at depth of 6 km in the Eocambrian evaporites. The floor thrust propagates upsection and merges in a roof thrust at depth of about 3 km in the Rawalpindi Group strata. The roof thrust has a hinterland vergence similar to backthrusts of the triangle zones in other fold-and-thrust belts. Integration of structural and timing data for consideration of kinematics suggests that thrust imbricate north of the preserved triangle zone is exposed due to increasing uplift and erosion of a duplex. A structural cross-section indicates that approximately 42 km of shortening has occurred across the NPDZ. The rate of shortening is 16 mm/yr considering deformation that has occurred between 4.5-1.9 Ma in the North Potwar Deformed Zone.